Return to work after occupational and non-occupational lower extremity amputation. (27th June 2018) - Journeay, W S; Pauley, T; Kowgier, M; Devlin, M
Abstract: Background: Factors impacting on return to work (RTW) after lower extremity amputation are important in occupational rehabilitation. Aims: Our objective was to compare RTW in patients who had traumatic work-related amputation with amputations from other causes. Methods: A retrospective cohort study was conducted with participants employed at the time of amputation and at least 1 year post-discharge from amputee rehabilitation. The primary outcome measure was RTW. Results: One hundred and forty-seven amputees were included with 69% returning to work. Amputation reason did not impact on RTW (odds ratio [OR] 1.83, P = non-significant). Trans-femoral amputees were less likely to RTW (OR 0.22, P < 0.05). Years since amputation (OR 1.20, P = 0.001) and Reintegration to Normal Living Index (OR 1.05, P < 0.001) were predictive of RTW after adjusting for other covariates. Conclusions: Amputation aetiology did not impact on RTW. Years since amputation, level of amputation and Return to Normal Living Index were associated with RTW which may be important to consider in RTW prognosis and planning.